UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA Kelas IV SDN 12 SUNGAI LIMAU - Nurleli Nurleli (STKIP Pesisir Selatan, 2019)
ABSTRACTBased on the learning outcomes of Class IV students of SDN 12 Sungai Limau in science subjects it was found that student learning outcomes in science subjects were still very low. The average student learning outcomes are still under the KKM. The purpose of this study was to describe and obtain information about efforts to improve student learning outcomes in science subjects through the Jigsaw Cooperative Learning Model in Class IV SDN 12 Sungai Limau. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subjects of the study consisted of 33 students in Class IV of SDN 12 Sungai Limau. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the Cooperative Learning Model Type Jigsaw can improve student learning outcomes in science subjects at SD N 09 Pasaman. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle were 46.42 (Less) increased to 84.33 (good) with an increase of 37.91%.